PENGARUH STRES KERJA, MOTIVASI KERJA DAN KEPEMIMPINAN TERHADAP KEPUASAN KARYAWAN PADA PT. PAMOR SPINNING MILLS KARANGANYAR - Jamillah Tri Khohari; Dewi Pujiani (Universitas Sahid Surakarta, 2019)
In this research has the objective to determine the effect of Work Stress, Work Motivation, and Leadership on Employee Satisfaction at PT. Pamor Spinning Mills Karanganyar.The hypothesis of this study is thought to influence of Work Stress, Work Motivation, and Leadership have an effect on significant to employee satisfaction at PT. Pamor Spinning Mills Karanganyar either in a persial or simultaneous manner. The result of the analysis in this study can be concluded that work stress, work motivation, and leadership have an effect on significant to employee satisfaction at PT. Pamor Spinning Mills Karanganyar. Necessary data in this study are primary data obtained with questionnaire method from a population of 100 responden. Analysis of the data used in this research is multiple linear regression test, t-test, f test and coefficient of determination.